Analysis of Herding Behavior on Post-Initial Public Offering (IPO) Shares in Indonesia Stock Exchange 2020-2022 - Nasution, Mhd. Fachri Akbar; Budiarta, Kustoro (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
This study aimed to investigate the existence of herding behavior in post-Initial Public Offering (IPO) stocks listed on the Indonesia Stock Exchange from 2020 to 2022. The research utilized the Cross-Sectional Absolute Deviation (CSAD) model to detect herding behavior. The population used in the research consisted of all companies that conducted an Initial Public Offering (IPO), with a sample of 164 companies conducting IPOs during the 2020-2022 period. Data collection techniques used daily closing stock price data and market closing price data for 30 days of observation, which were processed statistically using regression analysis and hypothesis testing with t-tests and determinant coefficients. The research results showed that there was no evidence of herding behavior during the observation period, as indicated by a non-linear, negative, and non-significant relationship between the dispersion value (CSAD) and squared market return (Rmt²). This indicated that investors tended to act rationally in making investment decisions on post-IPO shares.